The impact of urban agglomeration planning on depression in older adults - Liu, Ya; Yan, Li; Wang, Yujue; Tang, Xiaotang; Gao, Ming; Yang, Jiayu; Liu, Zuoyan; Hu, Xiuying (Frontiers in Public Health, 2024)
IntroductionThe residential environment significantly impacts the mental health of older adults. Urban agglomeration planning, while fostering regional economic development, also influences the psychological well-being of this demographic.MethodsThis study investigates the effects of urban agglomeration planning on depression levels in older adults, utilizing cohort data from the China Health and Retirement Longitudinal Study (CHARLS) and the multi-temporal double-difference-in-differences (DID) model.ResultsOur findings reveal that urban agglomeration planning alleviates depression by enhancing green spaces, improving air quality, and advancing digital infrastructure development. Moreover, these benefits are particularly pronounced among older females, residents of Central and Western regions, and those with lower educational attainment.ConclusionBased on our research findings, we recommend expediting the dissemination of urban agglomeration construction experiences to alleviate depression among older adults. In the implementation of policies, it is essential to consider objective conditions such as geographical location and educational level. The formulation of differentiated urban agglomeration planning to promote mental health among older adults.